Component-based modeling of PEM fuel cells with bond graphs - Vasilyev, A.; Andrews, John; Jackson, L.M.; Dunnett, S.J.; Davies, B. (Elsevier, 2017)
A polymer electrolyte membrane (PEM) fuel cell is a power generation device that transforms chemical energy contained within hydrogen and oxygen gases into useful electricity. The performance of a PEMFC unit is governed by three interdependent physical phenomena: heat, mass, and charge transfer. When modelling such a multi-physical system it is advantageous to use an approach capable of representing all the processes in a unified fashion.